The answer is: 5,614 square inches.
The explanation is shown below:
1. The gift on the bottom is a rectangular prism. To calculate its surface area, you must apply the following formula:
![SA=2[(l)(w)+(l)(h)+(h)(w)]](https://tex.z-dn.net/?f=SA%3D2%5B%28l%29%28w%29%2B%28l%29%28h%29%2B%28h%29%28w%29%5D)
Where
is the length (20 inches),
is the width (42 inches) and
is the heigth (16 inches).
2. Substitute values:
![SA1=2[(20in)(42in)+(20in)(16in)+(16in)(42in)]=3,664in^{2](https://tex.z-dn.net/?f=SA1%3D2%5B%2820in%29%2842in%29%2B%2820in%29%2816in%29%2B%2816in%29%2842in%29%5D%3D3%2C664in%5E%7B2)
3. The surface area of the other gifts can be calculated with the formula for calculate the surface area of a cube:
![SA=6s^{2}](https://tex.z-dn.net/?f=SA%3D6s%5E%7B2%7D)
Where
is the side.
4. The surface area of the bigger cube is:
![SA2=6(15in^{2})=1,350in^{2}](https://tex.z-dn.net/?f=SA2%3D6%2815in%5E%7B2%7D%29%3D1%2C350in%5E%7B2%7D)
5. The surface area of the smaller cube is:
![SA3=6(10in^{2})=600in^{2}](https://tex.z-dn.net/?f=SA3%3D6%2810in%5E%7B2%7D%29%3D600in%5E%7B2%7D)
6. The total surface area (the combined surface area of the three gifts) is:
![SAt=SA1+SA2+SA3\\SAt=3,664in^{2}+1,350in^{2}+600in^{2}\\SAt=5,614in^{2}](https://tex.z-dn.net/?f=SAt%3DSA1%2BSA2%2BSA3%5C%5CSAt%3D3%2C664in%5E%7B2%7D%2B1%2C350in%5E%7B2%7D%2B600in%5E%7B2%7D%5C%5CSAt%3D5%2C614in%5E%7B2%7D)
I think the answer is that they are parallel
Let x represent the # of people in sid’s group: 200 - (16.25x + 6.50x) = 18.25
200 - 22.75x = 18.25
-22.75x = -181.75
x = about 8
if Sid is not included in the group, i think the answer is D. 7, but im not sure
Answer:
Option A: (-10,0)
Step-by-step explanation:
The given equation of the parabola is in the form of
where the focus is located at
. Therefore, the focus of the parabola is
.
Answer:
y > 2x + 3
Step-by-step explanation:
Okay, first let's simplify the equation by understanding the form.
y = mx + b is the form.
Currently we have 2x - y < -3, So we can subtract 2x on both sides to get
-y < -2x - 3
Let's multiply each term by -1 to get
y < 2x + 3, but wait! We have to flip the sign!
The answer is :
y > 2x + 3